Methodology for Calculating VRE Equivalent Feed-In Tariff Based on System Cost and Its Application - Yunzhou ZHANG; Ning CHEN; Bibin HUANG; Caixia WANG; Jiangtao LI (Zhongguo dianli)
Consuming VRE (variable renewable energy) must rely on regulatory and supporting power sources such as thermal power unit and pumped storage as well as the support of power grids. As a result, the investment and operation cost of conventional power units and power grids ( i.e, the system cost of VRE) are increased. However, the system cost has not been considered in the existing domestic economic evaluation indicators of VRE, which is not conducive to the effective allocation of the system costs and enhancing the internal enthusiasm of each entity to promote the consumption of VRE. This paper puts forward the conception of VRE equivalent feed-in tariff and the calculation methodology of system cost. An idea for allocating the system cost is proposed based on the equivalent feed-in tariff. The calculation results of typical provinces show that the VRE equivalent feed-in tariff is still higher than the benchmark price of coal-fired plant during 2020-2025, which is hard for utilization of renewable energy in state-set price. The proposed system cost allocating mechanism can stimulate the inner motivation of each entity to promote the consumption of VRE and help realize the high-quality development of renewable energy.